Efektivitas Media Quizizz terhadap Keaktifan Mahasiswa pada Pembelajaran Akidah Akhlak - Oktavia, Imelda; Fadilah Hannum H; ⁠Nurrahmi Azzahrah; Siti Hartinah; Nurul Mahfuza (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to address the low level of student activeness in Akidah Akhlak learning, which is characterized by limited participation, low responsiveness, and passive engagement during classroom activities. This research was conducted to examine the effectiveness of interactive quiz media based on Quizizz in enhancing student activeness and to provide an innovative digital learning alternative in Islamic education contexts. Design/methods– This study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 30 students of the Islamic Education Study Program enrolled in the Akidah Akhlak course. Data were collected through observation sheets measuring student activeness, documentation, and field notes. Data analysis was conducted using descriptive quantitative methods by calculating percentages of student activeness across cycles Findings – The results showed a significant improvement in student activeness after the implementation of Quizizz-based interactive quiz media. The percentage of active students increased from 30% in the pre-cycle to 60% in Cycle I and reached 85% in Cycle II. This indicates that Quizizz effectively enhances student engagement, participation, and responsiveness in learning. The iterative improvements across cycles confirm that integrating digital interactive media contributes positively to active learning environments.